A study of code-switching and code-mixing used on YouTube channel: A comparison of Indonesian YouTubers - Risna Afryanti; Bukhari Daud; Kismullah Abdul Muthalib (English Education Journal, 2021)
YouTube is one of the biggest platforms where people around the world can share informative videos. In YouTube, we can find the code-switching and code-mixing phenomenon easily. There are two dominant types of code-switching and code-mixing. The first type is code-switching and code-mixing used by Group 1: Indonesian YouTubers who live abroad, while the second type is code-switching and code-mixing used by Group 2: Indonesian YouTubers who live in the country.  This study aimed to find out which group switched and mixed language the most. The transcripts of the chosen YouTube video were the collected data. The qualitative method was used in this study, and the data were analyzed using document analysis based on the framework of Myers-Scotton (1993) and Muysken (2000). The result showed that Group 1 used code-switching and code-mixing the most, with a total of 288 pieces of data. Group 2 used code-switching and code-mixing with a total of 262 pieces of data. The most dominant type of code-switching used by both groups was intra-sentential, a total of 154 pieces of data. The less dominant type of code-mixing used was insertion, a total of 253 pieces of data.